Hydrothermal Synthesis of 1T-MoS2/Pelagic Clay Composite and Its Application in the Catalytic Reduction of 4-Nitrophenol - Nan Li (MDPI AG, 2021)
Pelagic clay is an emerging marine resource with strong hydrophilicity, fine particles and a large specific surface area. In this work, a 1T-MoS2/pelagic clay composite was fabricated by hydrothermal synthesis. In the composite, 1T-MoS2 nanosheets are evenly dispersed on the surface of the clay minerals, significantly reducing the agglomeration of MoS2. Compared with pure 1T-MoS2, the 1T-MoS2 nanosheets generated on the surface of pelagic clay have significantly smaller lateral dimensions and thicknesses. Moreover, the specific surface area is much larger than that of the pure 1T-MoS2 nanosheets fabricated by the same method, indicating that the active sites of the MoS2 sheets are fully exposed. In addition, the composite exhibited excellent hydrophilicity, leading to a high dispersibility in aqueous solutions. In this work, the composite was used as a catalyst in the reduction of 4-nitrophenol (4-NP), and the conversion of 4-NP reached up to 96.7%. This result shows that the 1T-MoS2/pelagic clay composite is a promising catalyst in a variety of reactions.